Constitution writing and conflict resolution - Jennifer Widner (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Over 1975-2003 nearly 200 new constitutions were drawn up in countries at risk of conflict, as part of peace processes and the adoption of multiparty political systems. The process of writing constitutions is considered to be very important to the chances of sustaining peace, and The Commonwealth and the US Institute for Peace have developed good practice guidelines in this area. These emphasize consultation, openness to diverse points of view and representative ratification procedures. But assessing the impact of constitution-writing processes on violence is methodologically difficult, since there are many channels of influence in the relationship. This paper reports on preliminary findings from an ongoing research project into the effects of processes in constitution-writing. Regression analysis is used to control for important contextual features such as differences in income levels and ethnic diversity across countries. A key finding is that differences in the degree of participation in the drafting of constitutions has no major effect on post-ratification levels of violence in some parts of the world, such as Europe, but does make a difference in Africa, the Americas, and the Pacific together. – constitutions ; Commonwealth ; democracy ; governance
Keywords: K19; N40; 330